Mathematics self-belief and mathematical creativity of university students: the role of problem-solving skills - Bright Asare; Yarhands Dissou Arthur; Benjamin Adu Obeng (Cogent Education)
Purpose: The paper investigates the influence of problem-solving skills on the bond between mathematics self-belief and mathematical creativity of university students. Problem-solving skills were used to moderate the bond between mathematics self-belief and mathematical creativity of university students. Design/methodology/approach: This study adopted a cross-sectional design, which was used to distribute questionnaires to the respondents. The target population comprised 2400 students, and the sample size was calculated to be 331 university students. Exploratory factor analysis and reliability analysis were performed using SPSS (v.23), while confirmatory factor analysis and discriminant validity analysis were also performed using Amos (v.23) in this study. A structural equational modeling (SEM) was run in Analysis of Moment Structure (Amos v.23) to analyze the hypothesized path. Findings: The results indicated that mathematics self-efficacy belief positively influenced the mathematical creativity of university students. Again, mathematics self-efficacy belief positively influenced university students’ problem-solving skills. Finally, problem-solving skills positively moderated the nexus between mathematics self-belief and mathematical creativity of university students. Practical implications: Since mathematics self-belief significantly influences both problem-solving abilities and mathematical creativity, educators should prioritize building students’ confidence in their mathematics abilities by incorporating activities that promote mastery experiences, such as project-based learning, group tasks, and real-life problem scenarios, which can enhance students’ belief in their ability to succeed in mathematics. Moreover, universities and educators should implement instructional methods that encourage critical thinking, reasoning, and problem-solving to boost creativity in mathematics. Originality/value: Past studies have largely focused on the influence of mathematics self-belief on problem-solving skills and mathematics creativity. Also, the influence of problem-solving skills on mathematics creativity; however, this study focused on how problem-solving skills influence (i.e. moderate) the bond between mathematics self-belief and mathematical creativity of university students.